GOING TO ECUADOR - Tusev, Aleksandar (2017)
Aleksandar Tusev was born in Melbourne, Australia, to his loving parents Vasil and Todorka Tusev. He began his career as an accountant. During these years, he came to appreciate the importance of understanding how finance impacts people’s lives. After leaving the accounting field, Aleksandar returned to university to undertake study in the field of international relations. In 2010, he went on an exchange semester to Universidad de Espíritu Santo (UEES) in Guayaquil, Ecuador. The experience made a marked impression, so much so that he decided to move to Ecuador permanently. In 2012, Aleksandar moved to the nation’s capital Quito, spending a total of three years there where he worked as a professor at the University of the Americas (UDLA). In 2015 Aleksandar returned to Guayaquil after being accepted as a professor at UEES, the very same university where he started out as an exchange student five years earlier. At UEES, Aleksandar has committed himself to researching Ecuadorian culture and contemporary social issues. Going forward, he is cautiously optimistic that Ecuador will overcome the many societal problems it faces today, and become a source of inspiration for other developing nations around the world.